Diseño de un sistema de gestón integrado basado en las normas NTC ISO 9001: 2015, NTC ISO 14001:2015 y el decreto 1072 de 2015 para la microempresa Surtiapliques (2017)
Surtiapliques IS a metal-mechanc s stay on a static a ministration, to meet w the requirements of the current and future markets, it is proposed the design of an Integrated Management System between the areas of Quality by process standardization and meet ng customer requirements based on the NTC ISO 9001:2015, Safety and Health at Work, complying with the current mandatory legislation as Decree 1072 of 2015; at the environmental level implementing the Cleaner Production strategy with special emphasis on good Manufacturing practices and applying NTC ISO 14001:2015. By aligning these systems, there is a high probability of growth and permanence in the ndustrial sector aimed at sustainable development, from the beginning to the end of the production process Integral solutions are presented developed since diagnosis, analysis and operational development, based on theoretical, qualitative, quantitative and statistical methods, these are embodied in the documentary design of the Integrated System, that is ooking for satisfy all the stakeholders from the process approach in order to improve the effectiveness of the business management